PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA MASA PANDEMI COVID-19 DI HOTEL EASTIN ASHTA RESORT CANGGU BALI - Gilbert Efadri Utusan; A.A.Ratih Wijayanti; Putu Agus Prayogi; Isa Wahjoedi Dwi Poetranto (Journal of Tourism and Interdiciplinary Studies, 2023)
This research aims to determine the effect of work discipline and motivation on employee performance during the Covid-19 pandemic at the Eastin Ashta Resort Canggu Hotel. The research data was collected through questionnaires, the number of samples used was 46 people from the total population. The data obtained were tested first with validity test, reliability test and classical assumption test. After that the data were analyzed by multiple linear regression, T test and F test using the SPSS (Statistical Package for Sosial Science) version 25 for Windows program. Based on the results of the analysis, it is known that: (1) Workforce Discipline (X1) partially has a positive and significant effect on Employee Performance during the Covid-19 pandemic at the Eastin Ashta Resort Hotel Canggu Bali. This is evidenced by the value of t-count = 4.514 > t-table = 2.017 and the value of Sig. = 0.000 < 0.05 (α). (2) Motivation (X2) partially has a positive and significant effect on employee performance during the covid-19 pandemic at the Eastin Ashta Resort Canggu Bali. This is evidenced by the value of t-count = 2.505 > t-table = 2.017 and the value of Sig. 0.016 < 0.05 (α). (3) Work Discipline (X1) and Motivation (X2) simultaneously affect employee performance during the covid-19 pandemic at the Eastin Ashta Resort Canggu Bali. This is evidenced by the value of f-count = 20.916 > f-table = 3.23 and the value of Sig. 0.000 < 0.05 (α).